TUNA SUSILA (PSK) SEGMENTATION PHENOMENON BASED ON AGE AND USER: STUDY OF SOCIAL PATHOLOGY IN MILENIAL COMMUNITIES - Ridho Agung Juwantara (Raheema, 2022)
This research aims to explain about how new media became a social inequality factor that portrayed the market trading system in social phenomena. The emergence of new media in the community give the indirect fragmentation for the perpetrators of the deaf (Commercial Sex Workers). Based on the evidence obtained directly said that the current intensity of the role of Commercial Sex Workers people over the age of 40 years more favored by users from the lower middle class such as drivers and students. This is solely because the tariff installed by the workers of the participants over 40 years tends to be more accessible than the aged under 40 years. This phenomenon occurs after the advancement of technology that increasingly facilitate the community, especially the CSW under the age of 40 to take advantage of more opportunities by raising their rates for more capital in terms of beauty with purchase all kinds of fashion and brand-quality body care equipment through an online marketplace that can be easily accessed. This anomaly became interesting to be further researched about the impact that is, the emergence of new markets created due to new opportunities filled by the CSW over 40 years where they are more interested by users among the lower middle classes. This phenomenon shows the existence of social inequality which is influenced by social phenomena due to the rapid development of new media which also results in the poor image of Islam adopted by prostitutes.